2018
DOI: 10.20960/nh.1560
|View full text |Cite
|
Sign up to set email alerts
|

Early Nutrition Support Therapy in Patients With Head-Neck Cancer

Abstract: patients who receive ENS keep their nutritional condition instead of associated effects due to RT. ENS represents an efficient treatment and could prevent malnutrition associated comorbidities in oncologic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, the nutritional status of patients is difficult to improve significantly. Some prospective studies have demonstrated the significant effects of early nutritional intervention on RIOM and nutritional status in HNC patients undergoing RT (85,86). Early nutritional interventions can lead to higher serum albumin and hemoglobin levels in HNC patients (87).…”
Section: Early Nutritional Interventionmentioning
confidence: 99%
“…However, the nutritional status of patients is difficult to improve significantly. Some prospective studies have demonstrated the significant effects of early nutritional intervention on RIOM and nutritional status in HNC patients undergoing RT (85,86). Early nutritional interventions can lead to higher serum albumin and hemoglobin levels in HNC patients (87).…”
Section: Early Nutritional Interventionmentioning
confidence: 99%
“…Head and neck cancer (HNC) includes cancer of the oral cavity, pharynx, larynx, hypopharynx, and paranasal sinus [1]. Some risk factors have been described, including smoking, alcohol abuse, and human papillomavirus (HPV) infection [1,2]. HPV plays a role in the development of a subset of HNCs and, notably, oropharyngeal cancer (OPC) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The patients with HNC are particularly at risk of malnutrition due to the basic disease and complications of the oncological treatment such as radiotherapy (RT) or concurrent chemoradiotherapy (CRT). According to the literature, malnutrition is noted in 30-50% of HNC patients, especially located in the oropharynx and the hypopharynx [1]. It is caused by insufficient food intake due to dysphagia, odynophagia, and a lack of appetite caused by the tumor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations